PENGEMBANGAN KARIR TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR MELALUI MEDIASI WORK ENGAGEMENT PADA PEGAWAI DINAS PERUMAHAN DAN KAWASAN PERMUKIMAN PROVINSI MALUKU - Manumara, Anggita; Rahawarin , Mohamad Arsad; Tuanaya, Wahab (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2026)
This study aims to analyze the influence of career development on organizational citizenship behavior through work engagement mediation on employees of the Housing and Settlement Service of Maluku Province. This study uses a descriptive-quantitative approach with a causal correlation type, meaning that the relationship between the independent variable and the dependent variable is a causal relationship. The population used in this study were all ASN of the Housing and Settlement Service of Maluku Province totaling 62 people. The sampling method is full sampling. Data were analyzed using path analysis. The results of the study concluded that (1) Career development has a positive and significant effect on employee OCB, (2) Career development has a positive and significant effect on employee work engagement, (3) Work Engagement has a positive and significant effect on employee OCB and (4) Career development has a positive and significant effect on OCB through Work Engagement of employees of the Housing and Settlement Service of Maluku Province.